2015
DOI: 10.2151/sola.2015-027
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Precipitation Characteristics in Bangladesh from 1950 to 2008

Abstract: We analyzed trends in precipitation characteristics at 12 weather stations in Bangladesh using data from 1950 to 2008 and a non-parametric Mann-Kendall's tau test. It was found that the annual precipitation amount and the number of wet days tended to increase at almost all the stations. The number of days with weak precipitation (< 3 mm) showed increasing tendency; the number of days with daily precipitation exceeding 10 mm increased at three stations; and the number of days with daily precipitation exceeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…This perception is supported by data collected at national level on the climate in Bangladesh. Data from the Bangladesh Meteorological Department (BMD) for the periods of 1951–2011 show that for any ten-year period the temperature was higher and rainfall less predictable than in the preceding ten years [ 36 ]. Other countries such as Jamaica, Vietnam, and Nepal reported identical findings for their studies among a similar population [ 23 , 28 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This perception is supported by data collected at national level on the climate in Bangladesh. Data from the Bangladesh Meteorological Department (BMD) for the periods of 1951–2011 show that for any ten-year period the temperature was higher and rainfall less predictable than in the preceding ten years [ 36 ]. Other countries such as Jamaica, Vietnam, and Nepal reported identical findings for their studies among a similar population [ 23 , 28 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the frequency and intensity of extreme P events have shown an increasing trend in mainland China over the last few decades [35][36][37][38]. Similarly, the increasing trend of P extremes has been reported over Bangladesh in recent years [39][40][41]. In addition, Deshpande et al [42] reported a positive trend in extreme P events in India during the period of 1951-2013.…”
Section: Introductionmentioning
confidence: 95%
“…There are some regions in Bangladesh where every steps of agricultural activities from field preparation to harvesting of crops dependents on rainfall [4]. An earlier study conducted by Endo et al (2015) reported that heavy rainfall index showed no clear trend, and was dominated by inter-annual and/or decadal variations [5].…”
Section: Introductionmentioning
confidence: 99%